Cooperative ARQ protocol based on switch and stay node selection in WSN - HU Ying-bo1; CAI Yue-ming1 (Tongxin xuebao)
A cooperative automatic repeat request（ARQ） protocol based on switch and stay node selection（SSNS-CARQ） was proposed,which could obtain high energy efficiency and reliable transmission at the same time.A Markov model for analyzing the system throughput was built,and system throughput performance of the proposed protocol and the traditional ARQ protocol were analyzed based on such model.Based on a widely used energy consumption model in WSN,the energy consumption performance of SSNS-CARQ protocol and the traditional ARQ protocol were discussed and compared in terms of energy efficiency,and the effects that positions of relay nodes imposed on energy efficiency were also disscussed.Numerical and simulation results validated the Markov model effective for analyzing the system throughput.It is shown that SSNS-CARQ protocol could perform better in terms of throughput and energy efficiency when compared with the traditional ARQ protocol through simulations.